1984
DOI: 10.1007/978-3-642-69132-4_32
|View full text |Cite
|
Sign up to set email alerts
|

Human Pharmacokinetics and Safety of Boric Acid

Abstract: Using an in vitro technique it has been demonstrated that water-emulsifying and hydrophobic ointments containing boric acid liberate only minute amounts (1-6%) within 24 h compared with the nearly total liberation from a jelly. When an amount of boric acid containing ointment is swallowed, the absorption is only slightly delayed compared with a similar intake when dissolved in water, and in both cases nearly total excretion is found in the urine within 96 h. The halflife (t1l2/3) is 21 h (mean, 7 adult men). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 5 publications
2
14
0
3
Order By: Relevance
“…Five days later, the plasma concentration had fallen to 4 ppm, and the patient had excreted about 1.5 g of boron. The half-life of boron in this poisoning case was calculated to be about 29 hr, very near the half-life of boron in dogs as reported by Pfeiffer et al (23) and in humans as reported by Schou et al (25). (Figure 1).…”
Section: Introductionsupporting
confidence: 82%
“…Five days later, the plasma concentration had fallen to 4 ppm, and the patient had excreted about 1.5 g of boron. The half-life of boron in this poisoning case was calculated to be about 29 hr, very near the half-life of boron in dogs as reported by Pfeiffer et al (23) and in humans as reported by Schou et al (25). (Figure 1).…”
Section: Introductionsupporting
confidence: 82%
“…29 The pharmacological properties of BA, including ease of handling, low toxicity, an almost complete clearance via urine within 24 hours and the fact that it is not metabolized make it an attractive cancer treatment candidate. 28,[35][36][37][38][39] To date, five published studies have focused on the potential of BA to control progression of cancer at the cellular level. 17,18,20,21,40 Of these, only one study examined the ability of BA to inhibit prostate cancer cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the safety of boric acid in ordinary use is supported by a survey of dermatologists (4), by recent studies of ophthalmic ointments (8), by dermatologic use of ointments * Corresponding author. on neonates (5), and by two pharmacokinetic studies of oral (14) and intravenous (9) optical density measurements to give approximately 106 CFU/ml of sample. From 0.1 to 0.5 ml of the standardized suspension was then added to each 100-ml portion of minimal medium.…”
mentioning
confidence: 99%